Antifriction wear-resistant coating on titanium alloy surface and preparation method thereof

By laying a multi-layer friction-reducing and wear-resistant coating on the surface of the titanium alloy matrix, the failure problem of titanium alloy materials in high load and high wear environments is solved, and significant wear resistance and corrosion resistance are improved.

CN119571264APending Publication Date: 2025-03-07XIAN RARE METAL MATERIALS RES INST CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411782106.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

Titanium alloy materials can easily lead to premature failure of transmission system components under high load and high wear environments. The existing hard coatings are prone to cracks or peeling under high impact loads, and there are problems such as wear and corrosion coupling damage and insufficient bonding strength under corrosive environments.

Method used

The friction-reducing and wear-resistant coating is adopted, which is stacked on the surface of the titanium alloy base layer, the Cr-N metal cermet composite gradient transition layer, the Cr-C-N gradient intermediate layer and the Cr-C composite top layer, and the wear resistance and corrosion resistance of the coating are improved through the combination of the gradient structure and the amorphous carbon phase.

Benefits of technology

It significantly improves the service performance of the titanium alloy matrix, enhances the bonding strength and toughness of the coating, improves wear resistance and corrosion resistance, reduces the friction coefficient and extends the service life of the coating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119571264A_ABST
    Figure CN119571264A_ABST
Patent Text Reader

Abstract

The invention provides an antifriction and wear-resistant coating on a titanium alloy surface and a preparation method of the antifriction and wear-resistant coating, and belongs to the technical field of metal material surface protection. The antifriction and wear-resistant coating on the surface of the titanium alloy is prepared by adopting an ion plating technology and comprises a CrTi alloy base layer, a Cr-N metal ceramic composite gradient transition layer, a Cr-C-N gradient middle layer and a Cr-C composite top layer which are sequentially stacked on the surface of a titanium alloy matrix; wherein in the direction away from the titanium alloy matrix, the material of the Cr-N metal ceramic composite gradient transition layer is transited from Cr to CrN, the percentage content gradient of N atoms in the Cr-C-N gradient intermediate layer is reduced, the percentage content gradient of C atoms in the Cr-C gradient intermediate layer is increased, and the content of C atoms in the Cr-C composite top layer is not lower than 60 at.%. The antifriction and wear-resistant coating on the surface of the titanium alloy can improve the service performance of a titanium alloy matrix.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of metal material surface protection, and in particular to a friction-reducing and wear-resistant coating on the surface of a titanium alloy and a preparation method thereof. Background Art

[0002] Titanium alloys have become a key material in the field of light engineering equipment manufacturing due to their light weight, high strength, and excellent corrosion resistance in various environments. They are widely used in aerospace, petrochemical, offshore equipment, and high-precision parts processing. One of the main disadvantages of titanium alloy materials is their poor friction and wear performance. When titanium alloy transmission parts are in a high load and high wear environment for a long time, it is easy to cause premature failure of transmission system parts.

[0003] Physical vapor deposition (PVD) is used to plate hard coatings on titanium alloy transmission parts, which can significantly improve the wear resistance while maintaining the processing accuracy of the transmission parts. The currently widely used PVD coatings are mainly nitride coatings and DLC (Diamond-Like Carbon) coatings. Among them, the friction coefficient of nitride coatings is relatively large; although DLC coatings have the advantages of low friction and low wear, the DLC coating plating thickness is relatively low (≤3μm), and the coating stress is too large when high thickness is plated, which makes it difficult to meet the long-life protection requirements. Hard protective coatings will crack or even peel off under high impact loads, and will form wear-corrosion coupling damage in corrosive environments. At the same time, there is a problem of insufficient bonding strength with transmission parts, which limits the performance of the hard protective coating.

[0004] It should be noted that the information disclosed in the above background technology section is only used to enhance the understanding of the background of the present invention, and therefore may include information that does not constitute prior art known to ordinary technicians in the field. Summary of the invention

[0005] The purpose of the present invention is to overcome the deficiencies of the above-mentioned prior art, provide a friction-reducing and wear-resistant coating on the surface of a titanium alloy and a preparation method thereof, and improve the service performance of the titanium alloy substrate.

[0006] According to one aspect of the present invention, there is provided a friction-reducing and wear-resistant coating on the surface of a titanium alloy, comprising a CrTi alloy base layer, a Cr-N metal ceramic composite gradient transition layer, a Cr-CN gradient middle layer and a Cr-C composite top layer stacked in sequence on the surface of a titanium alloy substrate;

[0007] Wherein, along the direction away from the titanium alloy substrate, the material of the Cr-N metal ceramic composite gradient transition layer transitions from Cr to CrN;

[0008] Among them, along the direction away from the titanium alloy substrate, the percentage content of N atoms in the Cr-CN gradient intermediate layer decreases and the percentage content of C atoms increases;

[0009] The C atom content in the Cr-C composite top layer is not less than 60 at.%.

[0010] According to an embodiment of the present invention, the content of Cr in the CrTi alloy primer layer is a1, and a1≥50at.%; the thickness of the CrTi alloy primer layer is 0.2-2μm.

[0011] According to an embodiment of the present invention, the thickness of the Cr-N metal ceramic composite gradient transition layer is 0.5-2 μm.

[0012] According to one embodiment of the present invention, along the direction away from the titanium alloy substrate, the N content in the Cr-CN gradient intermediate layer decreases from a3 to a4, and the C content increases from 0 to a2; wherein a2 is between 40 and 60 at.%, a3 is between 30 and 50 at.%, and a4 is between 0 and 20 at.%.

[0013] According to one embodiment of the present invention, the thickness of the Cr-CN gradient intermediate layer is 0.5 to 5 μm, and the hardness is 25 to 35 GPa.

[0014] According to one embodiment of the present invention, the Cr-C composite top layer contains an amorphous carbon phase and an amorphous chromium carbide phase, and the atomic content of the amorphous carbon phase is higher than that of the amorphous chromium nitride phase.

[0015] According to one embodiment of the present invention, in the amorphous carbon phase contained in the Cr-C composite top layer, sp 2 Hybridized carbon atom content ≥ 60at.%;

[0016] The thickness of the Cr-C composite top layer is 1 to 6 μm;

[0017] When the Cr-C composite top layer rubs against the WC ceramic ball, the dry friction coefficient is as low as 0.12.

[0018] According to one embodiment of the present invention, the thickness of the CrTi alloy primer layer is 0.2 to 2 μm;

[0019] The thickness of the Cr-N metal ceramic composite gradient transition layer is 0.5 to 2 μm;

[0020] The thickness of the Cr-CN gradient intermediate layer is 0.5 to 5 μm;

[0021] The thickness of the Cr-C composite top layer is 1 to 6 μm;

[0022] The total thickness of the friction-reducing and wear-resistant coating is not less than 5 μm.

[0023] According to a second aspect of the present invention, there is provided a method for preparing the friction-reducing and wear-resistant coating on the surface of the titanium alloy, comprising the following steps:

[0024] S10, installing a titanium alloy substrate and a target material in a vacuum chamber of an ion plating machine, wherein the target material includes a Cr target material and a Ti target material;

[0025] Glow ion cleaning of S20, titanium alloy substrate and target;

[0026] S30, deposition of CrTi alloy base layer:

[0027] S40, depositing a Cr-N metal ceramic composite gradient transition layer; during the deposition process, the nitrogen flow rate is increased from 0 to 500-800 sccm;

[0028] S50, depositing a Cr-CN gradient intermediate layer; during the deposition process, the nitrogen flow rate is gradually reduced from 500-800 sccm to 50-300 sccm, and the acetylene flow rate is gradually increased from 0 to 50-200 sccm;

[0029] S60, depositing a Cr-C composite top layer; wherein, during the deposition process, the acetylene flow rate is 100 to 300 sccm.

[0030] According to an embodiment of the present invention, step S30 includes: in an argon gas flow atmosphere, turning on the Cr target and the Ti target, and setting the substrate bias voltage to -50 to -120 V, and depositing for 5 to 30 minutes;

[0031] Step S40 includes: turning on the Cr target, adjusting the argon flow rate to 500-1000 sccm, and setting the substrate bias voltage to -100--250 V; adjusting the nitrogen flow rate from 0 to 50-200 sccm during the initial deposition time of 10-20 minutes, and continuing to increase the nitrogen flow rate to 500-800 sccm during the subsequent deposition time of 10-30 minutes;

[0032] Step S50 includes: turning on the Cr target, adjusting the nitrogen flow rate from 500-800 sccm to 50-300 sccm within a deposition time of 30-150 min, adjusting the acetylene flow rate from 0 to 50-200 sccm, and adjusting the substrate bias voltage from -150-250 V to -50-120 V.

[0033] It is to be understood that both the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] The accompanying drawings herein are incorporated into and constitute a part of the specification, illustrate embodiments consistent with the present invention, and together with the specification are used to explain the principles of the present invention. Obviously, the accompanying drawings described below are only some embodiments of the present invention, and for those of ordinary skill in the art, other accompanying drawings can be obtained based on these accompanying drawings without creative work.

[0035] Figure 1 This is a schematic structural diagram of a friction-reducing and wear-resistant coating in one embodiment of the present invention.

[0036] Figure 2 This is a sample of the titanium alloy workpiece in Example 1, in which the surface of the titanium alloy workpiece is plated with a friction-reducing and wear-resistant coating.

[0037] Figure 3 This is a Rockwell indentation morphology of the friction-reducing and wear-resistant coating on the surface of the titanium alloy workpiece in Example 1.

[0038] Figure 4 This is a dry friction wear scar morphology of the friction-reducing and wear-resistant coating on the surface of the titanium alloy workpiece in Example 1.

[0039] Figure 5 This is a dry friction coefficient curve of the friction-reducing and wear-resistant coating on the surface of the titanium alloy workpiece in Example 1.

[0040] Figure 6 This is a Raman spectrum of the friction-reducing and wear-resistant coating on the surface of the titanium alloy workpiece in Example 1.

[0041] Figure 7 This is a morphology of the friction and wear scars of the anti-friction and wear-resistant coating on the surface of the titanium alloy workpiece in Example 1 in a seawater environment.

[0042] Figure 8 This is a curve of the friction coefficient of the anti-friction and wear-resistant coating on the surface of the titanium alloy workpiece in seawater environment in Example 1. DETAILED DESCRIPTION

[0043] Example embodiments will now be described more fully with reference to the accompanying drawings. However, the example embodiments can be implemented in a variety of forms and should not be construed as limited to the embodiments set forth herein; rather, these embodiments are provided so that the present invention will be comprehensive and complete and fully convey the concepts of the example embodiments to those skilled in the art. The same reference numerals in the figures represent the same or similar structures, and thus their detailed description will be omitted. In addition, the drawings are only schematic illustrations of the present invention and are not necessarily drawn to scale.

[0044] The terms "a", "an", "the", "said" and "at least one" are used to indicate the presence of one or more elements / components / etc.; the terms "including" and "having" are used to express an open-ended inclusion and mean that additional elements / components / etc. may exist in addition to the listed elements / components / etc.; the terms "first", "second" and "third" etc. are used merely as labels and are not intended to limit the quantity of their objects.

[0045] The embodiment of the present invention provides a friction-reducing and wear-resistant coating on the surface of a titanium alloy to improve the service performance of the titanium alloy substrate, and provides a method for preparing the friction-reducing and wear-resistant coating. Figure 1 The friction-reducing and wear-resistant coating includes a CrTi alloy base layer 11, a Cr-N metal ceramic composite gradient transition layer 12, a Cr-CN gradient middle layer 13 and a Cr-C composite top layer 14 which are sequentially stacked on the surface 10 of the titanium alloy substrate. In the direction away from the titanium alloy substrate, the material of the Cr-N metal ceramic composite gradient transition layer 12 transitions from Cr to CrN; in the direction away from the titanium alloy substrate, the percentage content of N atoms in the Cr-CN gradient middle layer 13 decreases and the percentage content of C atoms increases. In the Cr-C composite top layer, the C atom content is not less than 60 at.%.

[0046] In this embodiment, the friction-reducing and wear-resistant coating is a chromium-based multilayer protective coating, which combines the corrosion resistance of Cr metal, the high hardness and high load-bearing capacity of carbon / chromium nitride, and the friction-reducing advantages of amorphous carbon C. The friction-reducing and wear-resistant coating includes a CrTi alloy base layer 11 having a high bonding property with the titanium alloy surface to improve the bonding strength between the friction-reducing and wear-resistant coating and the titanium alloy substrate. In particular, the CrTi alloy base layer 11 can improve the matching between the titanium alloy substrate and the hard carbon / nitride layer (subsequent film layer), and enhance the bonding strength and toughness of the coating. The components in the Cr-N metal ceramic composite gradient transition layer 12 and the Cr-CN gradient intermediate layer 13 all show the characteristics of gradient transition, which can eliminate the strength mutation problem caused by the sudden change of the film material, thereby achieving a uniform transition of the film performance, which is conducive to the formation of a film layer of greater thickness, and thus is conducive to improving the wear resistance of the friction-reducing and wear-resistant coating. At the same time, the Cr-N metal ceramic composite gradient transition layer 12 has high corrosion resistance, and the Cr-CN gradient intermediate layer 13 has high load-bearing capacity, which can improve the service performance of the titanium alloy substrate in a high load and high wear environment, and further enhance the corrosion resistance of the titanium alloy substrate. The Cr-C composite top layer 14 is located on the surface of the friction-reducing and wear-resistant coating, which can be an amorphous Cr-C composite top layer 14 with a lower friction coefficient. In addition, the Cr-C composite top layer 14 not only has a better deposition rate advantage than the coating dominated by the carbon / chromium nitride ceramic phase, but also has good toughness, and has good wear resistance and friction reduction effects.

[0047] In one example, the titanium alloy substrate may be a titanium alloy transmission component, especially a titanium alloy transmission component used in a high-load, high-wear or high-corrosion environment for a long time.

[0048] In one embodiment of the present invention, ion plating technology can be used to sequentially form various film layers required for the friction-reducing and wear-resistant coating on the plated surface of the titanium alloy substrate, thereby improving the service performance of the titanium alloy substrate.

[0049] In one embodiment of the present invention, the friction-reducing and wear-resistant coating provided in the embodiment of the present invention can be prepared by the method shown in the following steps S10 to S60.

[0050] S10, installing a titanium alloy substrate and a target material in a vacuum chamber of an ion plating machine, wherein the target material includes a Cr target material and a Ti target material;

[0051] Glow ion cleaning of S20, titanium alloy substrate and target;

[0052] S30, depositing CrTi alloy base layer 11:

[0053] S40, depositing a Cr-N metal ceramic composite gradient transition layer 12; during the deposition process, the nitrogen flow rate is increased from 0 to 500-800 sccm;

[0054] S50, depositing a Cr-CN gradient intermediate layer 13; during the deposition process, the nitrogen flow rate is gradually reduced from 500 to 800 sccm to 50 to 300 sccm, and the acetylene flow rate is gradually increased from 0 to 50 to 200 sccm;

[0055] S60, depositing a Cr-C composite top layer 14; wherein, during the deposition process, the acetylene flow rate is 100-300 sccm.

[0056] In this embodiment, in step S40, nitrogen can be introduced into the vacuum chamber of the ion plating machine while depositing Cr, and the flow gradient of the introduced nitrogen gas is increased, so that the material of the prepared Cr-N metal ceramic composite gradient transition layer 12 transitions from Cr to CrN. For example, at the beginning of deposition, the content of Cr metal phase in the deposited film layer (belonging to the Cr-N metal ceramic composite gradient transition layer 12) is relatively high; as the nitrogen flow rate increases, the deposited film layer (belonging to the Cr-N metal ceramic composite gradient transition layer 12) presents a mixture of Cr metal phase and chromium nitride phases of different stoichiometric ratios (such as dichromium nitride, chromium nitride, etc.); as the nitrogen flow rate increases, the Cr metal phase in the deposited film layer (belonging to the Cr-N metal ceramic composite gradient transition layer 12) becomes less and less and eventually becomes substantially zero.

[0057] In this embodiment, in step S50, nitrogen and acetylene can be introduced into the vacuum chamber of the ion plating machine while Cr is deposited, and the flow gradient of the introduced nitrogen gas is reduced and the flow gradient of the introduced acetylene gas is increased. In this way, as the thickness of the Cr-CN gradient intermediate layer 13 increases, the N atomic percentage content gradient of the newly generated part decreases and the C atomic percentage content gradient increases.

[0058] In this embodiment, the friction-reducing and wear-resistant coating is prepared by ion plating technology, which has the advantages of high deposition rate, good winding properties, and high bonding strength with the substrate. It is particularly suitable for uniform plating of complex surfaces of titanium alloy transmission rods, and can still maintain good bonding strength on non-direct deposition surfaces.

[0059] In one embodiment of the present invention, the Cr content in the CrTi alloy base layer 11 is a1, and a1≥50 at.%; the thickness of the CrTi alloy base layer 11 is 0.2-2 μm. In the embodiment of the present invention, at.% represents atomic percentage.

[0060] In one embodiment of the present invention, the thickness of the Cr—N metal ceramic composite gradient transition layer 12 is 0.5-2 μm.

[0061] In one embodiment of the present invention, along the direction away from the titanium alloy substrate, the N content in the Cr-CN gradient intermediate layer 13 decreases from a3 to a4, and the C content increases from 0 to a2; wherein a2 is between 40 and 60 at.%, a3 is between 30 and 50 at.%, and a4 is between 0 and 20 at.%.

[0062] In one embodiment of the present invention, the Cr—CN gradient intermediate layer 13 has a thickness of 0.5 to 5 μm and a hardness of 25 to 35 GPa.

[0063] In one embodiment of the present invention, the Cr—C composite top layer 14 contains an amorphous carbon phase and an amorphous chromium carbide phase, and the atomic content of the amorphous carbon phase is higher than that of the amorphous chromium nitride phase.

[0064] In one embodiment of the present invention, the Cr—C composite top layer 14 is microscopically amorphous.

[0065] In one embodiment of the present invention, the C atom content in the Cr—C composite top layer 14 is 60 to 80 at.%.

[0066] In one embodiment of the present invention, in the amorphous carbon phase included in the Cr-C composite top layer 14, sp 2 The hybrid carbon atom content is ≥ 60 at.%; in particular, in the amorphous carbon phase contained in the Cr-C composite top layer 14, sp2 Hybridized carbon atom content ≥ 70at.%.

[0067] In one embodiment of the present invention, the thickness of the Cr-C composite top layer 14 is 1-6 μm; when the Cr-C composite top layer 14 rubs against a WC ceramic ball (tungsten carbide ceramic ball), the dry friction coefficient is as low as 0.12.

[0068] In one embodiment of the present invention, the thickness of the CrTi alloy base layer 11 is 0.2 to 2 μm;

[0069] The thickness of the Cr-N metal ceramic composite gradient transition layer 12 is 0.5-2 μm;

[0070] The thickness of the Cr-CN gradient intermediate layer 13 is 0.5-5 μm;

[0071] The thickness of the Cr-C composite top layer 14 is 1 to 6 μm;

[0072] The total thickness of the friction-reducing and wear-resistant coating is not less than 5 μm.

[0073] In the embodiment of the present invention, the gradient change of the element content may be a linear continuous change as the thickness changes, or may be a step-wise discontinuous change according to different film thickness ranges.

[0074] The present invention adopts ion plating deposition technology, and can adjust the density and energy of Cr, C, and N plasma in the vacuum chamber by adjusting at least one of the parameters such as substrate bias, arc target current, and reaction gas flow rate during the preparation of each film layer of the anti-friction and wear-resistant coating, thereby accurately adjusting the coating composition, structure, and density, and eliminating the strength-toughness mutation problem between the layers of the multi-layer structure coating. In addition, combining the excellent corrosion resistance of Cr metal, the high strength and high load-bearing characteristics of carbon / chromium nitride, and the self-lubricating characteristics of amorphous carbon (aC), a multi-layer structure of anti-friction and wear-resistant coating is constructed on the surface of titanium alloy transmission parts, which can significantly improve the service performance of titanium alloy transmission parts in multiple environments.

[0075] As follows, the preparation process of the friction-reducing and wear-resistant coating according to the embodiment of the present invention is exemplarily described.

[0076] In step S10, the type and quantity of target materials to be installed are selected according to the material, size and film thickness requirements of the titanium alloy substrate; Cr and Ti metal targets are selected to improve the bonding strength between the titanium alloy substrate and the protective coating. Strict pretreatment of the titanium alloy substrate is a necessary step for plating high-quality friction-reducing and wear-resistant coatings, which mainly includes polishing, rust removal and oil removal of the titanium alloy substrate (such as a titanium alloy workpiece) to ensure that the surface smoothness and cleanliness of the substrate meet the coating plating requirements. Another coating plating parameter that needs attention is the distance between the workpiece and the target surface, also known as the target-substrate distance, which will directly affect the plasma energy during the coating deposition process, and thus affect the coating performance.

[0077] In one embodiment of the present invention, in step S10, the distance between the arc target and the titanium alloy workpiece is set to 10-30 cm.

[0078] In one embodiment of the present invention, in step S10, the polished titanium alloy substrate is immersed in acetone and ethanol for ultrasonic cleaning for 10 to 20 minutes, dried with compressed air, and then placed on a rotating rack in a vacuum chamber of an ion plating machine.

[0079] In one embodiment of the present invention, in step S10, the purity of the Cr metal arc target and the Ti metal arc target is not less than 99.5%.

[0080] In step S20, a high voltage power supply can be used in a low vacuum environment to ionize the working gas to form a glow plasma discharge, and high-energy ions are used to remove the surface scale and contaminants on the surface of the titanium alloy. During the glow ion cleaning process, the arc target is turned on and the bias power supply is adjusted to bombard the substrate, which can firstly clean the arc target surface and secondly further clean the surface of the workpiece to be plated.

[0081] In one embodiment of the present invention, in step S20, the vacuum system and the heating system can be turned on, and the vacuum chamber temperature is 200-350°C and the vacuum degree is ≤5×10 -2 Pa, turn on the Cr arc target and Ti arc target, adjust the substrate bias to -400~-700V, and the bombardment time to 3~5min. After turning off the arc target, adjust the bias to -900V~-1200V, and use argon plasma to bombard and clean the titanium alloy substrate for 3~5min.

[0082] In one embodiment of the present invention, in step S20, when the Cr arc target and the Ti arc target are turned on, the arc target current is adjusted to 50-160A.

[0083] In step S30, considering the high bonding property with the surface of the titanium alloy substrate, CrTi alloy is selected as the metal base layer. When CrTi alloy is used as the base layer, the hardness, modulus and hardness-elasticity ratio can be changed by adjusting the components to adjust the matching property (thermal expansion coefficient, hardness) with the titanium alloy substrate.

[0084] In one embodiment of the present invention, step S30 includes: in an argon gas flow atmosphere, turning on the Cr target and the Ti target, setting the substrate bias voltage to -50 to -120 V, and depositing for 5 to 30 minutes.

[0085] In one embodiment of the present invention, in step S30, when the vacuum degree is less than 5×10 -3 When the vacuum chamber temperature is 300-450°C, 500-2000 sccm argon is introduced, the Cr arc target and the Ti arc target are turned on, the substrate bias is adjusted to -50--120 V, and the deposition time is 5-20 min.

[0086] In step S40, a Cr-N metal ceramic composite gradient transition layer 12 can be deposited. On the one hand, this can eliminate the problem of sudden change in strength and toughness between the CrTi alloy base layer 11 and the Cr-CN gradient intermediate layer 13; on the other hand, its excellent corrosion resistance can be utilized to improve its corrosion resistance in multiple environments.

[0087] In one embodiment of the present invention, step S40 includes: turning on the Cr target, adjusting the argon flow rate to 500-1000 sccm, and setting the substrate bias to -100--250 V; adjusting the nitrogen flow rate from 0 to 50-200 sccm during the initial deposition time of 10-20 minutes, and continuing to increase the nitrogen flow rate to 500-800 sccm during the subsequent deposition time of 10-30 minutes.

[0088] In one embodiment of the present invention, in step S40, the working gas pressure is maintained at 0.5-2Pa.

[0089] In step S50, a Cr-CN gradient intermediate layer 13 can be deposited. The hardness of chromium carbonitride can be adjusted in a large range, so the hardness value can be changed within the range of 25 to 35 GPa by adjusting the content of Cr, C, and N elements, thereby adjusting the components of chromium carbide, chromium nitride, and amorphous carbon, thereby meeting the high hardness and high load-bearing requirements of the anti-friction and wear-resistant coating. On the other hand, good friction reduction can be imparted by increasing the carbon content, eliminating the performance mutation between the Cr-C composite top layer 14. In addition, by adjusting the plasma energy, a uniform and dense cross-sectional morphology without columnar crystal features can be obtained, thereby improving the penetration of corrosive liquids into the anti-friction and wear-resistant coating.

[0090] In one embodiment of the present invention, step S50 includes: turning on the Cr target, adjusting the nitrogen flow rate from 500 to 800 sccm to 50 to 300 sccm within a deposition time of 30 to 150 minutes, adjusting the acetylene flow rate from 0 to 50 to 200 sccm, and adjusting the substrate bias voltage from -150 to -250 V to -50 to -120 V.

[0091] In one embodiment of the present invention, in step S50, the working gas pressure is maintained at 0.3-1.5 Pa.

[0092] In step S60, a Cr-C composite top layer 14 may be deposited. The Cr-C composite top layer 14 is a top layer composed of amorphous CrC and amorphous C, and has a hardness of 15 to 25 GPa. It has good wear resistance while maintaining a low friction coefficient. At the same time, the composite top layer 14 containing amorphous CrC and amorphous C has good toughness.

[0093] In one embodiment of the present invention, in step S60, during the deposition process, the acetylene flow rate is 100-300 sccm.

[0094] In one embodiment of the present invention, in step S60, the acetylene flow rate is adjusted to 100-300 sccm, the argon flow rate is adjusted to 500-1500 sccm, the bias voltage is adjusted to -100--250 V, and the deposition time is adjusted to 30-150 min.

[0095] In one embodiment of the present invention, the purity of the argon, nitrogen and acetylene is not less than 99.9%.

[0096] In one embodiment of the present invention, the current adjustment range of the target material (eg, arc target) is 50-160A.

[0097] In one embodiment of the present invention, after forming the Cr-C composite top layer 14, the vacuum system can be closed, and the temperature can be kept constant at 300-450°C for 0.5-1h and then cooled to break the vacuum when the vacuum chamber temperature is ≤120°C, and the titanium alloy workpiece can be taken out when the temperature drops to ≤60°C.

[0098] Embodiment 1:

[0099] The friction-reducing and wear-resistant coating on the titanium alloy surface shown in this embodiment includes a CrTi alloy base layer 11 with a thickness of 0.5 μm, a Cr-N metal ceramic composite gradient transition layer 12 with a thickness of 1 μm, a Cr-CN gradient intermediate layer 13 with a thickness of 2 μm, and a Cr-C composite top layer 14 with a thickness of 3 μm, which are sequentially deposited on a TC18 titanium alloy substrate.

[0100] The method for preparing the above-mentioned friction-reducing and wear-resistant coating on the surface of titanium alloy specifically comprises the following steps:

[0101] 1) Installing a titanium alloy substrate and a target: installing a Cr metal arc target with a purity of 99.9% and a Ti metal arc target with a purity of 99.9% in a vacuum chamber of an ion plating machine; immersing the polished TC18 titanium alloy workpiece (as a titanium alloy substrate) in acetone and ethanol for ultrasonic cleaning for 15 minutes in turn, drying it with compressed air, and placing it on a rotating rack in a vacuum chamber of the ion plating machine, and setting the distance between the arc target and the titanium alloy workpiece to be 10 to 20 cm;

[0102] 2) Glow ion cleaning of titanium alloy substrate and target: Turn on the vacuum system and heating system, wait until the vacuum chamber temperature is 200°C and the vacuum degree is 5×10 -2 At Pa, the Cr metal arc target and the Ti metal arc target were turned on, and the arc target current was set to 80-120A, the substrate bias was adjusted to -600V, and the bombardment time was 5min. After the arc target was turned off, the substrate bias was adjusted to -1100V, and the titanium alloy substrate was bombarded and cleaned with argon plasma for 5min.

[0103] 3) Deposition of CrTi alloy base layer 11: Wait until the vacuum degree is <5×10 -3 When the vacuum chamber temperature was 350°C, 1500 sccm of argon was introduced, the metal arc target was turned on, the Cr metal arc target current was adjusted to 120A, the Ti arc target current to 80A, the substrate bias voltage to -80V, and the deposition time to 10min;

[0104] 4) Depositing a Cr-N metal-ceramic composite gradient transition layer 12: the substrate bias voltage is -120 V, and the argon gas flow rate is 1000 sccm; during the initial 20-minute deposition time, the nitrogen gas flow rate is adjusted from 0 to 100 sccm; during the subsequent 15-minute deposition time, the nitrogen gas flow rate is further increased to 600 sccm to prepare a metal-ceramic composite gradient transition layer 12;

[0105] 5) Deposition of Cr-CN gradient intermediate layer 13: During the 80-min deposition time, the nitrogen flow rate was reduced from 600 sccm to 50 sccm, and the acetylene flow rate was increased from 0 to 180 sccm; the substrate bias was -170 V during the first 50-min deposition time and -120 V during the last 30-min deposition time, to prepare the Cr-CN gradient intermediate layer 13;

[0106] 6) Deposition of a Cr—C composite top layer 14: adjusting the acetylene flow rate to 180 sccm, the argon flow rate to 500 sccm, the substrate bias to -120 V, and the deposition time to 90 min to prepare a Cr—C composite top layer 14.

[0107] In this embodiment, Rockwell indentation morphology is also used to evaluate the bonding strength between the anti-friction and wear-resistant coating and the titanium alloy substrate. The load used is 100 kg, and the bonding strength of the coating reaches the HF1 standard. Figure 2 The sample of TC18 titanium alloy transmission rod with anti-friction and wear-resistant coating was displayed; Figure 3 The Rockwell indentation morphology of the coating is shown. No obvious cracks appear around the indentation, indicating that the coating has good toughness.

[0108] Figure 4 The morphology of the TC18 titanium alloy substrate plated with anti-friction and wear-resistant coating after sliding friction with a WC dual ball in an atmospheric environment for 1 h is given. The wear scar surface is smooth and there is no obvious peeling area, indicating that the coating has excellent wear resistance, and the wear rate is 1×10 -6 mm 3 / N·m.

[0109] Figure 5 The dry friction coefficient curve of the anti-friction and wear-resistant coating is given, and the average friction coefficient is 0.12. The low friction coefficient of the anti-friction and wear-resistant coating is mainly derived from the lubrication effect of a large amount of amorphous carbon phase in the Cr-C composite top layer 14. The amorphous carbon phase is sp 2 Mainly C phase. Figure 6 This is the Raman spectrum of the anti-friction and wear-resistant coating. The typical D peak and G peak in the Raman spectrum indicate the presence of amorphous carbon.

[0110] The friction-reducing and wear-resistant coating of this embodiment has good friction-reducing performance in a seawater environment, and the lubricating products in the seawater during the friction process will significantly reduce the friction coefficient. Figure 7 The surface morphology of the wear scar after friction in seawater environment is given, and it is found that the surface of the wear scar is covered with a thin film. Figure 8 The friction coefficient in seawater environment is given. The friction coefficient in sliding friction process is as low as 0.08, and the wear rate is 8×10 -7 mm 3 / N·m.

[0111] In addition, the friction-reducing and wear-resistant coating of this embodiment has good corrosion resistance in seawater, with a corrosion potential of -0.05V and a corrosion current density of 8×10 -8 A / cm 2 .

[0112] Embodiment 2:

[0113] The titanium alloy surface friction-reducing and wear-resistant coating shown in this embodiment includes a CrTi alloy base layer 11 with a thickness of 0.6 μm, a Cr-N metal ceramic composite gradient transition layer 12 with a thickness of 1 μm, a Cr-CN gradient intermediate layer 13 with a thickness of 2 μm, and a Cr-C composite top layer 14 with a thickness of 3 μm, which are sequentially deposited on a TC4 titanium alloy substrate.

[0114] The method for preparing the above-mentioned friction-reducing and wear-resistant coating on the surface of titanium alloy specifically comprises the following steps:

[0115] 1) Installing a titanium alloy substrate and a target: installing a Cr metal arc target with a purity of 99.9% and a Ti metal arc target with a purity of 99.9% in a vacuum chamber of an ion plating machine; immersing the polished TC4 titanium alloy workpiece (as a titanium alloy substrate) in acetone and ethanol for ultrasonic cleaning for 15 minutes in turn, drying it with compressed air, and placing it on a rotating rack in a vacuum chamber of the ion plating machine, and setting the distance between the arc target and the titanium alloy workpiece to be 10 to 20 cm;

[0116] 2) Glow ion cleaning of titanium alloy substrate and target: Turn on the vacuum system and heating system, wait until the vacuum chamber temperature is 200°C and the vacuum degree is 5×10 -2 At Pa, the Cr metal arc target and the Ti metal arc target were turned on, and the substrate bias voltage was adjusted to -600 V. The bombardment time was 5 min. After the arc target was turned off, the substrate bias voltage was adjusted to -1100 V. The titanium alloy substrate was bombarded and cleaned with argon plasma for 5 min.

[0117] 3) Deposition of CrTi alloy base layer 11: Wait until the vacuum degree is <5×10 -3 When the vacuum chamber temperature was 350°C, 1500 sccm of argon was introduced, the metal arc target was turned on, the Cr metal arc target current was adjusted to 120A, the Ti arc target current to 80A, the substrate bias voltage to -80V, and the deposition time to 10min;

[0118] 4) Depositing a Cr-N metal-ceramic composite gradient transition layer 12: the substrate bias voltage is -120 V, and the argon gas flow rate is 1000 sccm; during the initial 20-minute deposition time, the nitrogen gas flow rate is adjusted from 0 to 100 sccm; during the subsequent 15-minute deposition time, the nitrogen gas flow rate is further increased to 600 sccm to prepare a metal-ceramic composite gradient transition layer 12;

[0119] 5) Deposition of Cr-CN gradient intermediate layer 13: During the 80-min deposition time, the nitrogen flow rate was reduced from 600 sccm to 50 sccm, and the acetylene flow rate was increased from 0 to 180 sccm; the substrate bias was -170 V during the first 50-min deposition time and -120 V during the last 30-min deposition time, to prepare the Cr-CN gradient intermediate layer 13;

[0120] 6) Deposition of a Cr—C composite top layer 14: adjusting the acetylene flow rate to 180 sccm, the argon flow rate to 500 sccm, the substrate bias to -120 V, and the deposition time to 90 min to prepare a Cr—C composite top layer 14.

[0121] The bonding strength of the prepared protective coating with the TC4 substrate reached HF1, the dry friction coefficient was 0.13, and the corresponding wear rate was 9×10 -7 mm 3 / N·m.

[0122] Embodiment 3:

[0123] The titanium alloy surface friction-reducing and wear-resistant coating shown in this embodiment includes a TC4 titanium alloy substrate and a 0.6μm thick CrTi metal base layer, a 1μm thick Cr-N metal ceramic composite gradient transition layer 12, a 2μm thick Cr-CN gradient intermediate layer 13, and a 3μm thick Cr-C composite top layer 14 deposited thereon in sequence.

[0124] The preparation method of the titanium alloy surface protective coating structure specifically comprises the following steps:

[0125] 1) Installing a titanium alloy substrate and a target: installing a Cr metal arc target with a purity of 99.9% and a Ti metal arc target with a purity of 99.9% in a vacuum chamber of an ion plating machine; immersing the polished TC4 titanium alloy workpiece (as a titanium alloy substrate) in acetone and ethanol for ultrasonic cleaning for 15 minutes in turn, drying it with compressed air, and placing it on a rotating rack in a vacuum chamber of the ion plating machine, and setting the distance between the arc target and the titanium alloy workpiece to be 10 to 20 cm;

[0126] 2) Glow ion cleaning of titanium alloy substrate and target: Turn on the vacuum system and heating system, wait until the vacuum chamber temperature is 200°C and the vacuum degree is 5×10 -2 At Pa, the Cr metal arc target and the Ti metal arc target were turned on, and the substrate bias voltage was adjusted to -600 V. The bombardment time was 5 min. After the arc target was turned off, the substrate bias voltage was adjusted to -1100 V. The titanium alloy substrate was bombarded and cleaned with argon plasma for 5 min.

[0127] 3) Deposition of CrTi alloy base layer 11: Wait until the vacuum degree is <5×10 -3 When the vacuum chamber temperature was 350°C, 1500 sccm of argon was introduced, the metal arc target was turned on, the Cr metal arc target current was adjusted to 120A, the Ti arc target current was adjusted to 100A, the substrate bias voltage was -80V, and the deposition time was 10min;

[0128] 4) Depositing a Cr-N metal-ceramic composite gradient transition layer 12: the substrate bias voltage is -120 V, and the argon gas flow rate is 1000 sccm; during the initial 20-minute deposition time, the nitrogen gas flow rate is adjusted from 0 to 100 sccm; during the subsequent 15-minute deposition time, the nitrogen gas flow rate is further increased to 600 sccm to prepare a metal-ceramic composite gradient transition layer 12;

[0129] 5) Deposition of Cr-CN gradient intermediate layer 13: During the 80-min deposition time, the nitrogen flow rate was reduced from 600 sccm to 50 sccm, and the acetylene flow rate was increased from 0 to 120 sccm; the substrate bias was -170 V during the first 50-min deposition time and -120 V during the last 30-min deposition time, to prepare the Cr-CN gradient intermediate layer 13;

[0130] 6) Deposition of a Cr—C composite top layer 14: adjusting the acetylene flow rate to 180 sccm, the argon flow rate to 500 sccm, the substrate bias to -120 V, and the deposition time to 90 min to prepare a Cr—C composite top layer 14.

[0131] The bonding strength between the prepared coating and the TC4 substrate reached HF1, the dry friction coefficient was 0.15, and the corresponding wear rate was 3.6×10 -6 mm 3 / N·m.

[0132] Those skilled in the art will readily appreciate other embodiments of the present invention after considering the specification and practicing the invention invented herein. This application is intended to cover any modification, use or adaptation of the present invention, which follows the general principles of the present invention and includes common knowledge or customary techniques in the art that the present invention did not invent. The specification and examples are intended to be exemplary only, and the true scope and spirit of the present invention are indicated by the appended claims.

Claims

1. A friction-reducing and wear-resistant coating on the surface of a titanium alloy, characterized in that: It includes a CrTi alloy base layer, a Cr-N metal ceramic composite gradient transition layer, a Cr-CN gradient middle layer and a Cr-C composite top layer which are sequentially stacked on the surface of a titanium alloy substrate; Wherein, along the direction away from the titanium alloy substrate, the material of the Cr-N metal ceramic composite gradient transition layer transitions from Cr to CrN; Among them, along the direction away from the titanium alloy substrate, the percentage content of N atoms in the Cr-CN gradient intermediate layer decreases and the percentage content of C atoms increases; The C atom content in the Cr-C composite top layer is not less than 60 at.%.

2. The friction-reducing and wear-resistant coating on the surface of titanium alloy according to claim 1, characterized in that: The content of Cr in the CrTi alloy primer layer is a1, and a1≥50at.%; the thickness of the CrTi alloy primer layer is 0.2-2μm.

3. The friction-reducing and wear-resistant coating on the surface of titanium alloy according to claim 1, characterized in that: in, The thickness of the Cr-N metal ceramic composite gradient transition layer is 0.5-2 μm.

4. The friction-reducing and wear-resistant coating on the surface of titanium alloy according to claim 1, characterized in that: Along the direction away from the titanium alloy substrate, the N content in the Cr-CN gradient intermediate layer decreases from a3 to a4, and the C content increases from 0 to a2; wherein a2 is between 40 and 60 at.%, a3 is between 30 and 50 at.%, and a4 is between 0 and 20 at.%.

5. The friction-reducing and wear-resistant coating on the surface of titanium alloy according to claim 4, characterized in that: The thickness of the Cr-CN gradient intermediate layer is 0.5-5 μm, and the hardness is 25-35 GPa.

6. The friction-reducing and wear-resistant coating on the surface of titanium alloy according to any one of claims 1 to 5, characterized in that: The Cr-C composite top layer contains an amorphous carbon phase and an amorphous chromium carbide phase, and the atomic content of the amorphous carbon phase is higher than that of the amorphous chromium nitride phase.

7. The friction-reducing and wear-resistant coating on the surface of titanium alloy according to claim 6, characterized in that: The Cr-C composite top layer contains an amorphous carbon phase, sp 2 Hybridized carbon atom content ≥ 60at.%; The thickness of the Cr-C composite top layer is 1 to 6 μm; When the Cr-C composite top layer rubs against the WC ceramic ball, the dry friction coefficient is as low as 0.

12.

8. The friction-reducing and wear-resistant coating on the surface of titanium alloy according to claim 1, characterized in that: The thickness of the CrTi alloy base layer is 0.2 to 2 μm; The thickness of the Cr-N metal ceramic composite gradient transition layer is 0.5 to 2 μm; The thickness of the Cr-CN gradient intermediate layer is 0.5 to 5 μm; The thickness of the Cr-C composite top layer is 1 to 6 μm; The total thickness of the friction-reducing and wear-resistant coating is not less than 5 μm.

9. A method for preparing the friction-reducing and wear-resistant coating on the surface of titanium alloy according to claim 1, characterized in that: The following steps are involved: S10, installing a titanium alloy substrate and a target material in a vacuum chamber of an ion plating machine, wherein the target material includes a Cr target material and a Ti target material; Glow ion cleaning of S20, titanium alloy substrate and target; S30, deposition of CrTi alloy base layer: S40, depositing a Cr-N metal ceramic composite gradient transition layer; during the deposition process, the nitrogen flow rate is increased from 0 to 500-800 sccm; S50, depositing a Cr-CN gradient intermediate layer; during the deposition process, the nitrogen flow rate is gradually reduced from 500-800 sccm to 50-300 sccm, and the acetylene flow rate is gradually increased from 0 to 50-200 sccm; S60, depositing a Cr-C composite top layer; wherein, during the deposition process, the acetylene flow rate is 100 to 300 sccm.

10. The method for preparing the friction-reducing and wear-resistant coating on the surface of titanium alloy according to claim 9, characterized in that: Step S30 includes: in an argon gas flow atmosphere, turning on the Cr target and the Ti target, setting the substrate bias voltage to -50 to -120 V, and depositing for 5 to 30 minutes; Step S40 includes: turning on the Cr target, adjusting the argon flow rate to 500-1000 sccm, and setting the substrate bias voltage to -100--250 V; adjusting the nitrogen flow rate from 0 to 50-200 sccm during the initial deposition time of 10-20 minutes, and continuing to increase the nitrogen flow rate to 500-800 sccm during the subsequent deposition time of 10-30 minutes; Step S50 includes: turning on the Cr target, adjusting the nitrogen flow rate from 500-800 sccm to 50-300 sccm within a deposition time of 30-150 min, adjusting the acetylene flow rate from 0 to 50-200 sccm, and adjusting the substrate bias voltage from -150-250 V to -50-120 V.